The Conversion of Prothrombin in the Intrinsic System* - Müller, G. H (Thrombosis and Haemostasis, 1965)
A method is described for formation and partial isolation of intrinsic activator (I.A.). The term intrinsic activator of prothrombin conversion is used instead of blood thromboplastin to avoid ambiguity.The reaction of a purified prothrombin, I.A. and calcium in the thrombin formation is studied in different experiments. The following results are given as conclusion :A determinated amount of calcium is necessary for the full activity of the intrinsic activator. Calcium is probably fixed to the I.A. A too high concentration of calcium produces inhibition.The I.A. behaves as an enzyme in prothrombin conversion, prothrombin as a substrate.